THE ARCHIVAL FOUNDATION OF LITHUANIANEMIGRATION CATHOLIC AND LIBERAL IDEOLOGICALMOVEMENTS: RELEVANCE AND ACCESS - DAPKUTĖ, DAIVA; BUČINSKYTĖ, ILONA (Knygotyra, 2015)
Lithuanian culture facing the challenge of globalization carries an actual ambition of integration the Lithuanian emigrants’ heritage. The archival foundation is a part of it. The great interest in the culture, history and experiences of Lithuanian emigration emerged when Lithuania gained it’s independence in 1990. Now these days are gone. Only narrow circles of academic and public society still concern about the fate of Lithuanian emigration’s heritage. This paper deals with the archival foundation of two main Lithuanian ideological movements, which flourished among Lithuanian émigré after World War II. The problems of storage, relevance and access are discussed. Since the end of the 19th century the Lithuanian ideological landscape has been shaped by the movements of Catholic or liberal orientation. The clash between Catholic and liberal ideological trends increased during the period of the first Lithuanian Republic (1918–1940) and especially during the years of anti-Nazi resistAbstractance. The conflict of the ideologically orientated Catholics and liberals reached its peak during the years of emigration. The research points that despite the ideological disagreement the fate of the archival foundation of two Lithuanian emigration ideological movements is similar. During the years of action most of the ideological institutions’ didn’t pay special attention to the systematic storage of the archival foundation. It should be stated that the archival foundation of two Lithuanian emigration ideological movements is dispersed in the archival institutions in Lithuania and abroad and in the variety of personal archives. The materials kept in the archival institutions are available for the academics and public. The access to the archival documents kept in personal archives could be complicated. However, the fate of the private archives is the question of the ultimate concern. The death of the archive keeper often means the loss of an important and valuable historical and cultural material.